A phase II study of sorafenib in recurrent and/or metastatic salivary gland carcinomas: Translational analyses and clinical impact. (December 2016) - Locati, L.D.; Perrone, F.; Cortelazzi, B.; Bergamini, C.; Bossi, P.; Civelli, E.; Morosi, C.; Lo Vullo, S.; Imbimbo, M.; Quattrone, P.; Dagrada, G.P.; Granata, R.; et al.
Abstract: Background: Pre-clinical and clinical evidence suggests a rationale for the use of anti-angiogenic agents, including sorafenib, in recurrent and/or metastatic salivary gland carcinomas (RMSGCs). This study evaluates the activity of sorafenib in patients with RMSGCs and also investigates whether the activity of sorafenib could be related to its main tailored targets (i.e. BRAF, vascular endothelial growth factor receptor 2 [VEGFR2], platelet-derived growth factor receptor α [PDGFRα] and β, RET, KIT). Patients and methods: Patients received sorafenib at 400 mg BID. The primary end-point was response rate (RR) including complete response or partial response (PR); secondary end-points included RR according to Choi criteria, disease control rate (DCR), overall survival (OS), and progression-free survival (PFS). Results: Thirty-seven patients (19 adenoid cystic cancers, ACC) were enrolled. Six PRs were recorded. RR was 16% (95% confidence interval [CI]: 6–32; 11% in ACC and 22% in non-ACC). Choi criteria could be applied in 30 out of 37 cases with a RR of 50% (95% CI: 31–69%); DCR was 76% (95% CI: 59–88%). Incidence of ≥G3 adverse events was 29.7%. Median PFS and OS for the entire population were 5.9 months and 23.4 months, respectively. Median PFS and OS were 8.9 and 26.4 months for ACC versus 4.2 and 12.3 months for non-ACC patients. All the cases showed expression of PDGFRβ in the stroma and VEGFR2 in endothelial cells; PDGFRα positivity was found in the stroma of four (27%) cases. All except for two cases showed no PDGFRβ, VEGFR2 and PDGFRα expression in the tumour cells. KIT expression was restricted to ACC and a weak RET expression was limited to one adenocarcinoma, not otherwise specified (NOS). No BRAF mutation was found. No correlation was observed between the sorafenib activity and the expression of its markers although all six responders (two ACC, one adenocarcinoma, NOS, one salivary duct cancer [SDC], one high-grade mucoepidermoid [HG-MEC] and one poorly-differentiated cancer) are enriched in the stromal component showing a PDGFRβ immunodecoration. In ACCs, immunohistochemistry revealed MYB protein expression in 15/16 cases (94%) and the MYB-NFIB fusion oncogene was observed in 9/14 (64%). Conclusions: Sorafenib is the first anti-angiogenic agent to demonstrate activity in RMSGC patients, particularly in some histotypes such as HG-MEC, SDC and adenocarcinoma, NOS. The PDGFRβ-positive rich stromal component characterising these histotypes and the lack of correlation between the activity of sorafenib and its targets suggests anti-angiogenic effect as the prevalent mechanism of action of sorafenib in SGCs. Highlights: Anti-angiogenic agents may have a role in salivary gland carcinomas (SGCs). This study evaluates the activity of sorafenib in 37 recurrent and/or metastatic salivary gland carcinomas (RMSGCs) patients. Sorafenib showed activity in RMSGC patients, particularly in some histotypes. The anti-angiogenic effect may be the key mechanism of action of sorafenib in SGCs.